DINAMIKA SEKTOR INFORMAL Dl INDONESIA Prospek, Perkembangan, dan Kedudukannya dalam Sistem Ekonomi Makro - Agus Joko Pitoyo (Populasi, 2007)
Informal economy at long standing cannot be denied from thourough economic development in Indonesia. The informal sector has established since at the beginning of national development. Unideal structural transformation that was happened also becoming a triggering factor for mushrooming this sector. The existence of informal sector indeed has provided abundant employment opportunity. For most urban and rural job seekers, informal sector has become main job alternatives. This fact has globally emerging at macro economic development. Unsurprisingly, the economical prospect of this sector has enabled people to acheieve better standard of living. Based on Susenas data, this article focuses on the dynamic of informal sector related to its prospect, progress over time, and position in economic development.